2018
DOI: 10.1016/j.inoche.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of [Cu2(2,2′-bipyridine-N,N′)2(H2O)2(μ2-OH)2](barbiturate)2·2H2O and [Cu(2,2′-bipyridine-N,N′)(H2O)(barbiturate-O)Cl]·2H2O

Abstract: Crystal structures of [Cu 2 (2,2'-bipyridine−N,N') 2 (H 2 O) 2 (μ 2-OH) 2 ](barbiturate) 2 •2H 2 O and [Cu(2,2'-bipyridine−N,N')(H 2 O)(barbiturate−O)Cl]•2H 2 O

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Hydrogen bonding plays an important role in these structures. BA − is coordinated as a ligand to a transition or group 12 metal in only eight known crystal structures, some of which have been determined more than once [28][29][30][31][32][33][34][35][36]; there are no reported cases of coordination of BA − to lanthanide, actinide, or p-block metals. Coordination is through oxygen in each case except for one copper complex, in which it is through nitrogen [29].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonding plays an important role in these structures. BA − is coordinated as a ligand to a transition or group 12 metal in only eight known crystal structures, some of which have been determined more than once [28][29][30][31][32][33][34][35][36]; there are no reported cases of coordination of BA − to lanthanide, actinide, or p-block metals. Coordination is through oxygen in each case except for one copper complex, in which it is through nitrogen [29].…”
Section: Introductionmentioning
confidence: 99%
“…24 They are widely used in crystal engineering as tectons because of the reliability of the hydrogen bonding patterns that they define. 25,26 Thiourea forms noncentrosymmetric complexes when combined with inorganic salts resulting in enhanced NLO activity. 27−31 The photoluminescence (PL) spectra showed that emission is in the blue region for some synthesized crystals of the thiourea metal complexes with a little Stokes shift.…”
Section: ■ Introductionmentioning
confidence: 99%